Interdiffusion coefficients and atomic mobilities in Fe-rich fcc Cu-Fe-Mn alloys - Zhang, Lijun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
In the present work, the interdiffusion coefficients in fcc Cu-Fe-Mn alloys were experimentally determined via a combination of solid/solid diffusion couples, electron probe microanalysis (EPMA) technique and Matano-Kirkaldy method. Based on the reliable thermodynamic description of fcc phase in the Cu-Fe-Mn system available in the literature as well as the ternary diffusion coefficients measured in the present work, the atomic mobilities in fcc Cu-Fe-Mn alloys were assessed by utilizing the DICTRA (Diffusion Controlled TRAnsformation) software package. The calculated interdiffusion coefficients based on the assessed atomic mobilities agree well with most of the experimental data. The comprehensive comparison between various model-predicted diffusion properties and the measured data, including the concentration penetration profiles, interdiffusion flux profile, and diffusion paths future verify the reliability of the presently obtained atomic mobilities.